INTERSECTING IDENTITIES: THE LIVED EXPERIENCES OF GAY, MALE CATHOLIC COLLEGE & UNIVERSITY ALUMNI - Kleine, Todd D. (2018)
This phenomenological study describes emergent themes related to how gay, male alumni perceive their experiences of attending an American Catholic institution of higher education. Utilizing a modified version of Seidman’s phenomenological interview protocol, six gay, male alumni of various American Catholic institution of higher education were interviewed in an attempt to arrive at the essence of attending a college or university where Church teachings and campus culture intersected with the sexual orientation of certain community members. From the collected data, four clear themes emerged: all alumni experienced pre-college negative messages about their sexual orientation, visibility and support were positive contributors to alumni experiences and technology played a key role in connecting with other gay men. Further, Catholic Church teachings as interpreted by campus administrators had multiple impacts on the experiences of the alumni throughout their time on campus. The findings of this study can be used by educational leaders at American Catholic institutions of higher education to create awareness and better inform policy and support program creation for this vulnerable minority population of students